2023
DOI: 10.1021/acs.inorgchem.3c00702
|View full text |Cite
|
Sign up to set email alerts
|

Methylammonium Cation-Regulated Controllable Preparation of CsPbBr3 Perovskite Quantum Dots in Polystyrene Fiber with Enhanced Water and UV Light Stabilities

Abstract: In situ fabrication of lead halide perovskite quantum dots (PQDs) is important for narrow-band emitters for LED displays due to the simple work procedure and convenient usability; however, the growth of PQDs is not readily controllable in the preparation, resulting in low quantum efficiency and environmental instability of PQDs. Here, we demonstrate an effective strategy to controllably prepare CsPbBr3 PQDs in polystyrene (PS) under the regulation of methylammonium bromide (MABr) via electrostatic spinning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Flexible and superior hydrophobic polymers such as polystyrene (PS), poly­(vinylidene fluoride) (PVDF), polydimethylsiloxane (PDMS), and poly­(methyl methacrylate) (PMMA) could be used as encapsulation materials, which allow the PNCs to survive in in vitro and in vivo aqueous environments with high luminescence efficiency but no lead leakage. For example, in 2017, Zhang et al reported a water-resistant microhemisphere strategy via embedding PNCs into the PS matrix for multicolor luminescence probes in live cells .…”
Section: Introductionmentioning
confidence: 99%
“…Flexible and superior hydrophobic polymers such as polystyrene (PS), poly­(vinylidene fluoride) (PVDF), polydimethylsiloxane (PDMS), and poly­(methyl methacrylate) (PMMA) could be used as encapsulation materials, which allow the PNCs to survive in in vitro and in vivo aqueous environments with high luminescence efficiency but no lead leakage. For example, in 2017, Zhang et al reported a water-resistant microhemisphere strategy via embedding PNCs into the PS matrix for multicolor luminescence probes in live cells .…”
Section: Introductionmentioning
confidence: 99%
“…Lead-halide perovskite nanocrystals (PNCs), with the formula APbX 3 [A = MA (methylammonium), FA (formamidinium), or Cs; X = Cl, Br, or I], have recently achieved tremendous success in a variety of applications covering solar cells, lasers, and light-emitting diodes (LEDs) due to their excellent photoelectric characteristics such as low formation energy, high photoluminescence quantum yield (PL QY), adjustable emission peak position, and narrow emission full width at half-maximum (fwhm) . In particular, the MAPbBr 3 PNCs exhibit the strongest structural stability in the lead-halide perovskite family, where the tolerance factor is close to 1.…”
Section: Introductionmentioning
confidence: 99%